RETRACTED: ZNF655 Promotes the Progression of Glioma Through Transcriptional Regulation of AURKA - Chen, Xu; Liu, Chao; Zhang, Zhenyu; Wang, Meng; Guo, Shewei; Li, Tianhao; Sun, Hongwei; Zhang, Peng (Frontiers in Oncology, 2022)
Objectives: Glioma has a high degree of malignancy, strong invasiveness and poor prognosis, which is always a serious threat to human health. Previous studies have reported that C2H2 Zinc finger (ZNF) protein is involved in the progression of various cancers. In this study, the clinical significance, biological behavior and molecule mechanism of ZNF655 in glioma were explored. Methods: The expression of ZNF655 in glioma and its correlation with prognosis were analyzed through public datasets and immunohistochemical (IHC) staining. The shRNA-mediated ZNF655 knockdown was used to explore the effects of ZNF655 alteration on the phenotypes and tumorigenesis of human glioma cell lines. Chromatin immunoprecipitation (ChIP)-qPCR and luciferase reporter assays were performed to determine the potential mechanism of ZNF655 regulating Aurora kinase A (AURKA). Results: ZNF655 was abundantly expressed in glioma tissue and cell lines SHG-44 and U251. Knockdown of suppressed the progression of glioma cells, which was characterized by reduced proliferation, enhanced apoptosis, cycle repression in G2, inhibition of migration, and weakened tumorigenesis. Mechanistically, transcription factor ZNF655 activated the expression of AURKA by directly binding to the promoter of AURKA. In addition, downregulation of AURKA partially reversed the promoting effects of overexpression of ZNF655 on glioma cells. Conclusions: ZNF655 promoted the progression of glioma by binding to the promoter of AURKA, which may be a promising target for molecular therapy.